The impact of a full-scale war on the Black sea ecosystems of Ukraine and the entire sea in general - Kharchenko, Viacheslav (My University, 2023)
The Russian full-scale invasion of Ukraine in February 2022 and the ongoing Russian-Ukrainian war have a significant impact on the Black Sea ecosystems, especially on their biotic component. About 87 % volume of the Black Sea are heavily anoxic. The northwestern part of the sea has the best conditions for the development of biota. This water area is well warmed by the sun's rays in the warm period of the year and rivers saturate seawater with dissolved oxygen and nutrients. This part of the sea is of decisive importance for the biota of the entire Black Sea. The impact of war on marine ecosystems is divided into two types: (i) the direct impact of the war – on the biota of the sea; (ii) the indirect impact of the war – on the ecosystems of the Black Sea. As direct impacts in this article are considered the effects of weapons, ammunition explosions (the shock waves, the sound of explosions), the use of powerful sonars – primarily on marine mammals (dolphins and porpoises – probably up to 50 000 cetaceans have already died). The consequences of oil spills due to the flooding and damage of warships and other military equipment, water pollution by toxic components of ammunition (heavy metals, polychlorinated biphenyls etc.), pathogens (as a bacteriological weapon or due to damage to the city sewer or an agricultural complexes), and possible radioactive contamination are considered as indirect impacts. The possibilities of spreading the indirect consequences of the war to non-Black Sea – Mediterranean – ecosystems are highlighted. Повномасштабне вторгнення Росії в Україну в лютому 2022 року та російсько-українська війна, яка триває, мають значний вплив на екосистеми Чорного моря, особливо на їх біотичну складову. Близько 87 % об’єму Чорного моря є сильно аноксичними. У північно-західній частині моря найкращі умови для розвитку біоти. Ця акваторія добре прогрівається сонячними променями в теплий період року, а річки насичують морську воду розчиненим киснем і поживні речовини. Ця частина моря має вирішальне значення для біоти всього Чорного моря. Вплив війни на морські екосистеми поділяють на два види: (i) прямий вплив війни – на морську біоту; (ii) непрямий вплив війни – на екосистеми Чорного моря. В якості прямого впливу в цій статті розглядається вплив зброї, вибухів боєприпасів (ударні хвилі, звук вибухів), використання потужних гідролокаторів – в першу чергу на морських ссавців (дельфінів і морських свиней – ймовірно, до 50 000 китоподібних вже загинуло). ). Наслідки розливів нафти внаслідок затоплення та пошкодження бойових кораблів та іншої військової техніки, забруднення води токсичними компонентами боєприпасів (важкими металами, поліхлорбіфенілами тощо), хвороботворними мікроорганізмами (як бактеріологічною зброєю або через пошкодження міської каналізації чи сільськогосподарських комплексів), а можливе радіоактивне забруднення розглядається як непрямий вплив. Висвітлюються можливості поширення непрямих наслідків війни на нечорноморські – середземноморські – екосистеми.
Keywords: Black sea ecosystems; impact of a full-scale war; conditions for the development of biota; marine mammals; екосистеми Чорного моря; вплив повномасштабної війни; умови для розвитку біоти; морські ссавці; кафедра екології та екоменеджменту